2019
DOI: 10.1109/access.2019.2907554
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Protocols Interworking With Open Connectivity Foundation in Fog Networks

Abstract: Intelligent applications have greatly promoted the development of fog computing. The protocols have emerged diversely, causing the problems in the interworking between terminal devices, which has seriously hindered the development of fog computing. Based on the open connectivity foundation (OCF) protocol, this paper proposes an interworking solution for intelligent devices and designs an OCFbased multi-protocol gateway to access non-OCF services. The main functions are divided into three categories: manager, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…The Wi-Fi has the great potential to provide connectivity to many IoT devices and things to achieve sustainability. These 802.11 Wi-Fi standardswhich can be utilized for sustainability IoT are shown below [31] [11], Open Connectivity Foundation (OCF) [43], the Thread Group [40], the Powerline technologies, and oneM2M. In a recent trail of high data rate communications, it has been shown that it is possible to achieve 100 Gb/s in microwave spectrum using multiple-input, multiple-output (MIMO) for a communication range of approximately 1 mile.…”
Section: Wi-fi Standardsmentioning
confidence: 99%
“…The Wi-Fi has the great potential to provide connectivity to many IoT devices and things to achieve sustainability. These 802.11 Wi-Fi standardswhich can be utilized for sustainability IoT are shown below [31] [11], Open Connectivity Foundation (OCF) [43], the Thread Group [40], the Powerline technologies, and oneM2M. In a recent trail of high data rate communications, it has been shown that it is possible to achieve 100 Gb/s in microwave spectrum using multiple-input, multiple-output (MIMO) for a communication range of approximately 1 mile.…”
Section: Wi-fi Standardsmentioning
confidence: 99%
“…In this regard, the interworking proxy is used for bridging OCF clients and servers [27]. In similar attempts, an OCF enabled multi-protocol gateway is developed by [28] for semantic conversion and protocol translation for accessing non-OCF services. Like wise [29] proposed a proxy framework for communication between edge nodes to provide interoperability among heterogeneous communication protocols.…”
Section: Background and Related Workmentioning
confidence: 99%
“…The EdgeX framework provides service-based microservices which enable multiple device proxies to be deployed in the EdgeX-based platform to handle corresponding platform-specific IoT edge networks [17]. Li et al [18] proposed an OCF-based multi-protocol gateway to access non-OCF services based the centralized management service to support the semantic conversion scheme in the translation process. Esquiagola et al [19] proposed an interception proxy including functions of transparent discovery communication between devices to extend the interaction capabilities of the IoT edge network for enabling the interoperability of heterogeneous communication protocols.…”
Section: Related Workmentioning
confidence: 99%